2010
DOI: 10.1177/1045389x10385485
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Testing of the Static Deflections of Circular Piezoelectric Unimorph Actuators

Abstract: In this article, based on the classical laminated plate theory, a new static deflection model for CPUAs subjected to voltage is established and the bonding layer is taken into account as an individual layer. According to the established analytical model, the influences of the structural parameters and material properties of the CPUA on the transverse deflection are numerically simulated and the static and dynamic characteristics of the CPUA are experimentally tested. The research results show that the predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…It is observed that the relationship between the flow rate and the back pressure is linear, as expected. Previous studies on valveless pumps [13,20] showed that the pump performance in the form of flow rate versus pressure is very close to a linear line. The results provide the limits of performance in terms of maximum flow rate (20 L/min) at zero back pressure and maximum back pressure (220 Pa) at zero flow rate.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…It is observed that the relationship between the flow rate and the back pressure is linear, as expected. Previous studies on valveless pumps [13,20] showed that the pump performance in the form of flow rate versus pressure is very close to a linear line. The results provide the limits of performance in terms of maximum flow rate (20 L/min) at zero back pressure and maximum back pressure (220 Pa) at zero flow rate.…”
Section: Resultsmentioning
confidence: 94%
“…A peristaltic micropump design with shape memory alloy as the actuator was presented by Sassa et al [18]. The mechanism of diaphragm vibration with piezoelectric actuators has been explained by Mo et al [19] and Wang et al [20]. The deflection of a circular diaphragm in case of a PZT actuator having smaller diameter than the diaphragm was discussed.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…When the pressure difference between the inlet and the outlet of the ACMV is not large, for example, the maximum pressure difference is only a few thousand pascals, the impact of the inlet fluid to deformation of the CPUA with the applied voltage of about 100 V can be ignored. To improve the accuracy of the model, taking into account the impact of the adhesive layer on the deflection of the CPUA as shown in Figure 5, we use the transverse deflection model for the partially covered CPUA with the clamped edge (Wang and Huo, 2010), which can be expressed as…”
Section: Modeling the Relationship Between The Gap Height And The Applied Voltagementioning
confidence: 99%
“…In previous works, Pan and Wang (2016) developed an active piezoelectric microfluidic valve with annular boundary and established an active control flow model based on a deflection mathematical model of partially covered circular piezoelectric unimorph actuator (CPUA) for the clamped support condition under voltage control (Wang and Huo, 2010). Based on this, the principle and structure of a PCB process-based microfluidic pump integrated into PCB are proposed and realized in this article.…”
Section: Introductionmentioning
confidence: 99%